An isolated bacterial consortium for crude oil biodegradation - Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Husain, Iman A. F. (2011)
Crude oil utilizing bacteria was isolated from crude-oil contaminated soil (COCS) and tested for their ability to degrade COCS. Fifty strains were isolated, purified and monitored on agar plated for their growth. Twenty strains selected for the second monitoring in shake flask using minimal salt medium with crude oil as sole carbon source. The growth was monitored by measuring the optical density (OD600) on daily basis. The twelve best growing strains were selected to form four bacterial consortiums. Each consortium contains three strains combined with accordance to their growth. The four consortiums were tested for their growth and the best one (Cons.1) was selected for the kinetics study and the biodegradability test. The first order kinetic study showed that the μmax of Cons.1 was 0.02 hr-1 while the half saturation constant ks was 2.2 %v/v TPH. The consortium proved a good biodegradation of crude oil in soil slurry with removal up to 95% which would further be used for the bioremediation of COCS.